An introduction to JavaScript [ - Casanova, Georgianna (New York : Learning Press, 2014)
This book introduces the reader to JavaScript
1. Introduction to JavaScript -- 2. JavaScript syntax -- 3. Client-side JavaScript and JavaScript engine -- 4. Ajax (programming) and cross-site scripting -- 5. JSDoc and JSON -- 6. Jscript, JsonML and seed (programming) -- 7. Unobtrusive JavaScript and XMLHttpReques
Keywords: JavaScript (Computer program language)